2011
DOI: 10.1007/s00125-011-2331-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between red blood cell distribution width and macrovascular and microvascular complications in diabetes

Abstract: Aims/hypothesis Red blood cell distribution width (RDW) has been reported to be a risk marker of morbidity and mortality for cardiovascular disease in various study populations. However, no studies have investigated the relationship between RDW and diabetes complications. We therefore evaluated RDW as a marker of macrovascular and microvascular complications in a nationally representative sample of the adult diabetes population in the USA. Methods A cross-sectional study was performed using the nationwide 1988… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
100
4
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(122 citation statements)
references
References 33 publications
(52 reference statements)
11
100
4
7
Order By: Relevance
“…It was reported that a 1% increment in RDW increased mortality risk by 14% regardless of hemoglobin concentration in all 7 studies of the metaanalysis. In the third National Health and Nutrition Examination Survey study, higher RDW values were found to be associated with an increased risk of developing nephropathy in patients with DM (18). In another prospective study, patients with diabetic foot osteomyelitis had higher RDW values by the end of 1 year compared to a control group (19).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that a 1% increment in RDW increased mortality risk by 14% regardless of hemoglobin concentration in all 7 studies of the metaanalysis. In the third National Health and Nutrition Examination Survey study, higher RDW values were found to be associated with an increased risk of developing nephropathy in patients with DM (18). In another prospective study, patients with diabetic foot osteomyelitis had higher RDW values by the end of 1 year compared to a control group (19).…”
Section: Discussionmentioning
confidence: 99%
“…RDW is a widely used laboratory parameter for the quantification of the extent of erythrocyte anisocytosis. Some studies have shown that RDW levels are an independent variant of prognosis in cases with cardiovascular diseases, type 2 diabetes mellitus, pulmonary thromboembolism and ischemic stroke (13,14). Additionally, It was found to be related to mortality and other severe adverse outcomes in infectious diseases (28).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation might disrupt red blood cell maturation, cell membrane damage throughly, causing RDW to increment. Different studies have reported that increased RDW levels, even within the normal reference range, were associated with unfavorable clinical outcomes in cases with cardiovascular diseases, type 2 diabetes mellitus, pulmonary thromboembolism and ischemic stroke (13,14). Nowadays, a number of variables have been studied as an inflammatory marker in AA (8,15,16) however the results are inconsistent.…”
mentioning
confidence: 99%
“…RDW was considered as a prognostic marker reflecting the underlying inflammatory event. It can be used in the evaluation of determining microvascular and macrovascular complications of DM [14].…”
Section: Discussionmentioning
confidence: 99%